Hydration characteristics, structural effects and the taste quality of some polyhydroxy compounds in aqueous solutions of nicotinic acid (vitamin B3) at (288.15–318.15) K. (25th April 2020) - Sharma, Mousmee; Banipal, Parampaul K.; Banipal, Tarlok S.
Highlights: Transfer parameters suggest the prevalence of hydrophilic-hydrophilic interactions. Nicotinic acid does not change the basic taste quality of polyhydroxy compounds. Interactions of studied compounds are weaker with nicotinic acid than other vitamins. Disaccharides have higher compressibility hydration numbers than monosaccharides. Hyperchromic shift has been observed in aqueous as well as buffer media. Abstract: Physicochemical properties elucidating the hydration characteristics and structural effects of polyhydroxy compounds in mixed aqueous solutions offer significant information for the growth of pharmaceutical and food industries. Consequently, standard partial molar volumes and isentropic compressibilities at infinite dilution of saccharides, their derivatives and sugar alcohols in (0.01, 0.05, 0.09 and 0.13) mol kg −1 nicotinic acid(aq) (vitamin B3) solutions have been investigated by experimental density and ultrasonic velocity with respect to temperature. Their transfer values, compressibility hydration numbers, apparent massic volumes and isentropic compressibilities have also been determined. These parameters are important to study the taste behavior of polyhydroxy compounds and intermolecular interactions occurring in ternary mixtures. UV absorption spectra of the studied polyhydroxy compounds have been recorded in 1 × 10 −4 mol kg −1 nicotinic acid(aq) solutions. The comparison of present results has been made with the studies reported earlier in l -ascorbic acid, thiamine HCl and pyridoxine HCl.